Territorial Rationalities: Mining Laws in two Argentinean Provinces - de la Vega, Candela (Sociedad y Economía, 2013)
Public policies about territory contain and prescribe specific rationalities, that is to say,generating principles of social practices, codes of vision, decision and action, whichin turn constitute themselves in allowed, expected or legitimized criteria. This articleshows a comparative analysis of the existing convergences between current State miningdecisions in two Argentinean provinces: Cordoba and La Rioja. The particularity of thesetwo cases is that while in Córdoba applies a prohibiting open-pit mining law; in La Rioja,there is a law that enabled this activity. This analysis was carried through a study of thecontent of legal texts and depth interviews conducted to civil servants.